The emergence of COVID-19 over-concern immediately after the cancelation of the measures adopted by the dynamic zero-COVID policy in China - Hao, Fengyi; Zhang, Zhisong; Lau, Sam S. S.; Chiang, Soon-Kiat; Zhou, Dewen; Tan, Wanqiu; Tang, Xiangdong; Ho, Roger (Frontiers in Public Health, 2024)
Background This study aimed to report the prevalence of COVID-19 over-concern and its associated factors after the relaxation of the health-protective measures in China. Methods A team of seven experts in psychiatry and psychology specializing in COVID-19 mental health research from China, Hong Kong, and overseas reached a consensus on the diagnostic criteria for COVID-19 over-concern. Individuals had to meet at least five of the following criteria: (1) at least five physical symptoms; (2) stocking up at least five items related to protecting oneself during the COVID-19 pandemic; (3) obsessive-compulsive symptoms related to the COVID-19 pandemic; (4) illness anxiety related to the COVID-19 pandemic; (5) post-traumatic stress symptoms; (6) depression; (7) anxiety; (8) stress and (9) insomnia. An online survey using snowball sampling collected data on demographics, medical history, views on COVID-19 policies, and symptoms of COVID-19 over-concern. Multivariate linear regression was performed using significant variables from the previous regressions as independent variables against the presence of COVID-19 over-concern as the dependent variable. Breush-Pagan test was used to assess each regression model for heteroskedasticity of residuals. Results 1,332 respondents from 31 regions in China participated in the study for 2 weeks from December 25 to 27, 2022, after major changes in the zero-COVID policy. After canceling measures associated with the dynamic zero-COVID policy, 21.2% of respondents fulfilled the diagnostic criteria for COVID-19 over-concern. Factors significantly associated with COVID-19 over-concern were poor self-rated health status (β = 0.07, p < 0.001), concerns about family members getting COVID-19 (β = 0.06, p < 0.001), perceived usefulness of COVID-19 vaccine (β = 0.03, p = 0.012), impact on incomes, employment and studies (β = 0.045, p < 0.001) and impact on families (β = 0.03, p = 0.01). Conclusion After removing measures associated with the dynamic zero-COVID policy in China, approximately one-fifth of respondents met the diagnostic criteria for COVID-19 over-concern.